2013
DOI: 10.1111/aos.12261
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopy of conjunctiva in preservative‐free timolol 0.1% gel formulation therapy for glaucoma

Abstract: ABSTRACT.Purpose: To evaluate the effects at 1 year of preservative-free timolol gel and preserved timolol eye drops on conjunctiva and tear parameters. Methods: Forty patients with primary open-angle glaucoma or ocular hypertension were randomized to the two treatment groups and compared with 20 healthy age-matched controls. Clinical tests (IOP, Schirmer I test, and lacrimal film break-up time BUT) and in vivo conjunctival confocal microscopy (IVCM) were performed in all patients at baseline and after 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
0
27
0
3
Order By: Relevance
“…This toxicity may be the reason for increased expressions of MMPs and TIMPs in the epithelium of glaucoma patients. Further, switching antiglaucoma medication to eye drops that contain a different preservative (Aihara et al 2013) or to preservative-free solutions (Mastropasqua et al 2013;Frezzotti et al 2014) might be beneficial for the maintenance of tissue integrity and health in the superficial parts of the eye. Thus, in addition to long-term treatment with multiple different eye drops, the preservative BAK itself may contribute to our results.…”
Section: Discussionmentioning
confidence: 99%
“…This toxicity may be the reason for increased expressions of MMPs and TIMPs in the epithelium of glaucoma patients. Further, switching antiglaucoma medication to eye drops that contain a different preservative (Aihara et al 2013) or to preservative-free solutions (Mastropasqua et al 2013;Frezzotti et al 2014) might be beneficial for the maintenance of tissue integrity and health in the superficial parts of the eye. Thus, in addition to long-term treatment with multiple different eye drops, the preservative BAK itself may contribute to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Other common modifications involve nerve plexus alterations and collagen deposition inducing fibrosis [11]. All these chronic inflammatory alterations may negatively influence the surgical outcome thus increasing the possibility of surgical failure by altering the aqueous humor (AH) flow through the bleb wall [12].…”
Section: Introductionmentioning
confidence: 99%
“…11 Different authors have shown that the lack of BAK in the drops can improve the ocular surface of glaucomatous patients. 15,24,25 Our results suggest that a single-dose tear supplement may reduce the damaging effects of the preservative BAK on conjunctival cells, on the tear film, and on sensory nerve fibers with alteration of the threshold of excitability, which follows a reduced sensitivity. Since corneal sensitivity and the number of nerve fibers in the cornea and BUT improved, a tear film supplement might be associated to a better corneal function.…”
Section: Discussionmentioning
confidence: 71%